2007
DOI: 10.1016/j.chom.2007.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Tumor Domain-Containing Viral Proteases Evade Ubiquitin- and ISG15-Dependent Innate Immune Responses

Abstract: Ubiquitin (Ub) and interferon-stimulated gene product 15 (ISG15) reversibly conjugate to proteins and mediate important innate antiviral responses. The ovarian tumor (OTU) domain represents a superfamily of predicted proteases found in eukaryotic, bacterial, and viral proteins, some of which have Ub-deconjugating activity. We show that the OTU domain-containing proteases from nairoviruses and arteriviruses, two unrelated groups of RNA viruses, hydrolyze Ub and ISG15 from cellular target proteins. This broad ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
432
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 318 publications
(452 citation statements)
references
References 53 publications
17
432
3
Order By: Relevance
“…Interestingly, here we found that the PL2 cysteine protease domain of Nsp2 was responsible for IFN antagonism. This result is consistent with a previous report that PRRSV Nsp2 deconjugates ubiquitin and ISG15 from cellular target proteins (Frias-Staheli et al, 2007). Therefore, the PL2 domain of Nsp2 not only acts as a viral protease and deubiquitinating (DUB) enzyme, but can also inhibit the induction of type I IFN.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Interestingly, here we found that the PL2 cysteine protease domain of Nsp2 was responsible for IFN antagonism. This result is consistent with a previous report that PRRSV Nsp2 deconjugates ubiquitin and ISG15 from cellular target proteins (Frias-Staheli et al, 2007). Therefore, the PL2 domain of Nsp2 not only acts as a viral protease and deubiquitinating (DUB) enzyme, but can also inhibit the induction of type I IFN.…”
Section: Discussionsupporting
confidence: 82%
“…Nsp2 aa 47-240 (Tyr47-Cys240) and Nsp2 aa 47-323 (Tyr47-Leu323) are required to maintain the trans-and cis-cleavage activities, respectively (Han et al, 2009). The PL2 protease of PRRSV Nsp2 is thought to be a new member of the ovarian tumour (OTU) protease superfamily, capable of deconjugating ubiquitin and ISG15 (Frias-Staheli et al, 2007). The highly conserved amino acids among OTU members are located at the putative Cys55-His124 catalytic motif of Nsp2.…”
Section: Introductionmentioning
confidence: 99%
“…The full-length sequence encoding the N protein was cloned into pCAGGS for mammalian expression. The plasmids expressing the full-length L protein or the truncation mutants HA-L (1-1325), HA-L (1325HA-L ( -2590 and HA-L (2590-3945) have been described previously (Frias-Staheli et al, 2007). The mutant HA-L (1-1325) DZF was generated by site direct mutagenesis (Stratagene), according to the manufacturer's instructions, changing cysteine in positions 609 and 613 for alanine.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore we attempted to characterize this interaction and determine which regions within the L protein mediate the N-L association. For this purpose, we utilized three plasmids expressing haemagglutinin (HA)-tagged L protein truncation mutants (Frias-Staheli et al, 2007) (Fig. 1a).…”
Section: Analysis Of the N-l Interactionmentioning
confidence: 99%
See 1 more Smart Citation